Contaminants fingerprinting in environmental matrices of Radon concentration in groundwater: A baseline study in Alappuzha (Kerala) and the associated health effects - Selvam Sekar; Akhila V. Nath; Muthukumar Perumal; Priyadarsi D. Roy; Amin Ullah; Muralitharan Jothimani (PLoS ONE, 2026)
Accumulation of Radon in groundwater from aquifer lithologies can pose significant health risks. This study investigates its concentration in coastal Alappuzha from the Kerala state in India to assess health risks from ingestion and inhalation in groundwater samples of both the pre-monsoon and post-monsoon seasons. The activity(RAD7detector)in post-monsoon samples remained relatively higher (2.59–66.46 Bq/L; average:20.25 Bq/L) compared to the pre-monsoon (1.63–46.38 Bq/L; average: 13.78 Bq/L), reflecting the effect of precipitation on enhanced Radon contamination. However, the samples presently do not exceed the World Health Organization recommended maximum value (100 Bq/L). Relatively higher average radiation doses for stomach and lungs (6.12–6.20 Svy -1 ) in post-monsoon samples compared to pre-monsoon (4.12–4.22 Svy -1 ) show more exposures in the post-monsoon season. Our estimations of the total effective dose from two different pathways provide valuable baseline data on radon exposure in a coastal region of India, where health risks could increase due to higher precipitation and more frequent heavy rainfall events in the near future. Such conditions may enhance groundwater recharge and promote the downward migration of radon-rich soil gases into aquifers, potentially elevating radon concentrations, particularly in uranium-bearing lithological settings.